Factors Strategic Choice and Impact at Quality of Higher Education - الطائي علي حسون; رؤوف محمد عماد (Journal of Economics and Administrative Sciences, 2018)
This research raised the strategic selection factors and dimensions of the quality of higher education and what the nature of their relationship and has been collecting a sample search from the technological University of president scientific departments and administrative and scientific associates and chiefs of branches This research aims at studying factors affecting the strategic selection effects these factors in the quality of higher education and the combination of these factors has been identified as a group of selected dimensions of quality of higher education and study link relationships and affecting factors and strategic selection of (risk, previous strategies, resources, time, considerations and internal trends) and dimensions of the quality of higher education (senior management commitment, the participation of workers, training , Measurement and analysis, continuous improvement) and the data were analyses using the SPSS statistical software and tools used for analysis are: determining the saturation factor, arithmetic mean, standard deviation, coefficient of variation, simple linear correlation coefficient Spearman to test the validity of hypotheses and affecting link analysis and hypothesis testing adopted in research which proved the existence of a link between research variables and the effects were statistically acceptable degree which shows the importance of choosing strategic alternative within the dimensions of the quality of higher education researcher has come to several conclusions of which he found there is interest in using Application of maybes quality of higher education quality in the Organization discussed, either by the most important recommendations was the need for constant comparisons to handle risk situations that may affect the selection of the appropriate strategic alternative in addition to make good quality strategic goals discussed in organization’s reach